2016
DOI: 10.1002/pssb.201600017
|View full text |Cite
|
Sign up to set email alerts
|

Negative Poisson's ratio in cubic materials along principal directions

Abstract: This report employed molecular statics simulation and densityfunctional-theory calculation to study the Poisson's ratios of face-centered-cubic materials. We provide numerical and theoretical evidences to show that cubic materials can exhibit auxetic behavior in a principal direction under proper loading conditions. When a stress perpendicular to the loading direction is applied, cubic materials can exhibit a negative Poisson's ratio at finite strain. The negative Poisson's ratio behavior, including its direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 34 publications
(39 reference statements)
1
23
0
Order By: Relevance
“…This means that the systems might lend themselves to some potential niche applications which require sudden changes in transverse dimensions upon reaching some critical load, such as smart sensors. Auxeticity which occurs after reaching some extent of applied strain has also been demonstrated before in other materials and structures at nanoscale as well as macroscale which also exhibit negative Poisson's ratio at finite strain …”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…This means that the systems might lend themselves to some potential niche applications which require sudden changes in transverse dimensions upon reaching some critical load, such as smart sensors. Auxeticity which occurs after reaching some extent of applied strain has also been demonstrated before in other materials and structures at nanoscale as well as macroscale which also exhibit negative Poisson's ratio at finite strain …”
Section: Resultssupporting
confidence: 72%
“…Auxeticity which occurs after reaching some extent of applied strain has also been demonstrated before in other materials and structures at nanoscale as well as macroscale which also exhibit negative Poisson's ratio at finite strain. [79][80][81][82][83][84][85] All this is very significant since it has been shown that these hierarchical nanoscale honeycombs, where the lower level is provided through a truss system exhibits some very useful properties, which when combined with other properties characteristic of polyphenylactylenes (e.g., the high conductivity due to the extensive electronic delocalisation of these systems) make them ideal for potential use in a number of applications which would require such systems. These could range from nanofilters (these systems benefit from the presence of zeolitelike pores which have dimensions in the nm scale) to components in electronic devices.…”
Section: Resultsmentioning
confidence: 99%
“…17 NPR was found to be intrinsic to single-layer black phosphorus due to its puckered configuration, which leads to NPR in the out-of-plane direction.…”
Section: 16 Thementioning
confidence: 99%
“…There has been a wide range of structures with bulk form showing auxeticity based on different mechanisms including structures with re‐entrant geometry, theoretical models, structures with rigid rotating units, hinge structures and elastic instability . Some crystalline materials also exhibit auxeticity in some directions . Recently, the investigation of auxetic property of nanoscale materials and structures using both numerical simulations and experiments have been received considerable attention .…”
Section: Introductionmentioning
confidence: 99%